2019
DOI: 10.1007/s12011-019-01963-5
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Status and Hypothyroidism: A Systematic Review and Meta-analysis

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 52 publications
0
40
0
3
Order By: Relevance
“…Of the 8 men with overt hyperthyroidism, only 1 (12.5%) were under treatment. Mean, median and range of participants treated with thiamazole were respectively 7.5 (±1.0), 7.5 (5)(6)(7)(8)(9)(10), and range of 5 to 10 mg. Of the 183 incident cases of hypothyroidism, 49 (26.8%) were identified based on TSH and FT4 levels and 134 (73.2%) were identified by use of medication. Of them, 142 (77.6%) were women and 113 (79.6) of them where under treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 8 men with overt hyperthyroidism, only 1 (12.5%) were under treatment. Mean, median and range of participants treated with thiamazole were respectively 7.5 (±1.0), 7.5 (5)(6)(7)(8)(9)(10), and range of 5 to 10 mg. Of the 183 incident cases of hypothyroidism, 49 (26.8%) were identified based on TSH and FT4 levels and 134 (73.2%) were identified by use of medication. Of them, 142 (77.6%) were women and 113 (79.6) of them where under treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Selenium can also affect metabolic disorders through its association with thyroid hormone function [10,44]. Hypothyroxinaemia has been found to be associated with obesity [45], and a meta-analysis by Talebi et al found significantly lower levels of Se in patients with hypothyroidism compared to healthy people [46].…”
Section: Discussionmentioning
confidence: 99%
“…Sample size determination was based on a parallel design randomized controlled trial where type I and II error rates were considered to be 5 and 20% (statistical power of 80%), respectively. According to a past study (Machin, Campbell, Tan, & Tan, 2018; Spaggiari et al, 2017; Talebi, Ghaedi, et al, 2019; Talebi, Karimifar, et al, 2020), we considered the minimum detectable standardized effect size for LT4 dose to be 0.8. With regard to formula, we needed a minimum of 26 participants per group.…”
Section: Methodsmentioning
confidence: 99%
“…As well, hypothyroidism is represented a potential risk of obesity (Sanyal & Raychaudhuri, 2016). Untreated hypothyroidism is linked to various clinical signs, like constipation, fatigue, weight gain, infertility, depression, and bradycardia (Gaitonde, Rowley, & Sweeney, 2012; Talebi, Ghaedi, et al, 2019; Talebi, Karimifar, Heidari, Mohammadi, & Askari, 2020). However, many patients, despite being treated with adequate thyroid hormone replacement, still experience hypothyroid‐related symptoms, affecting patient quality of life (Freeman, Adunlin, Mercadel, Danzi, & Klein, 2019).…”
Section: Introductionmentioning
confidence: 99%